Percutaneous Transhepatic Biodegradable Stent Placement for Benign Anastomotic Biliary Strictures: Short-Term Outcomes of a Single-Institution Experience - Mohammad Arabi; Bassam Alrehaili; Refaat Salman; Shahbaz Qazi; Omar Bashir; Khalid Abdullah; Mohammad Almoaiqel (The Arab Journal of Interventional Radiology)
Purpose: The purpose of this study was to assess the safety and effectiveness of biodegradable stents in the management of benign anastomotic biliary strictures. Materials and Methods: This retrospective study included all consecutive adult patients who underwent percutaneous biodegradable stent insertion for benign anastomotic biliary strictures that were refractory to cholangioplasty or biliary drainage-dependent or preferred stent placement to avoid long-term tube dependence. Fourteen stents were used in 12 patients (9 males) with a mean age of 53 years (range: 23–72 years). Ten patients had liver transplant (7 – choledochocholedochal anastomosis and 3 – hepaticojejunal anastomosis). Two patients had primary sclerosing cholangitis with hepaticojejunal anastomosis. The mean time since surgery was 5.5 years (6 months–16 years). Ten patients had an average of three (range: 1–6) previous sessions of biliary dilatation. Two patients initially preferred stent placement to avoid long-term tube dependence. Results: Technical and clinical success was achieved in all cases. One patient died 2 months after stent insertion because of progressive liver cirrhosis. No re-intervention was required in 8 (72%) of the remaining 11 patients at a mean follow-up time of 234 days (96–539 days). Three liver transplant patients required re-intervention at a mean time of 287 days. There were one severe procedure-related complication (cholangitis and sepsis) and one mild complication (transient septicemia). Stent migration into the bowel occurred in one case a few days after insertion, but this required no re-intervention. No procedure-related mortality occurred. Conclusion: Biodegradable biliary stent may offer a safe and effective option to avoid tube dependence in patients with benign anastomotic biliary strictures.